2011
DOI: 10.1007/s12185-011-0883-y
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of myeloperoxidase and gene mutations in AML patients with normal karyotype: double CEBPA mutations are associated with high percentage of MPO positivity in leukemic blasts

Abstract: The percentage of myeloperoxidase (MPO)-positive blast cells is a simple and highly significant prognostic factor in AML patients. It has been reported that the high MPO group (MPO-H), in which >50% of blasts are MPO activity positive, is associated with favorable karyotypes, while the low MPO group (≤50% of blasts are MPO activity positive, MPO-L) is associated with adverse karyotypes. The MPO-H group shows better survival even when restricted to patients belonging to the intermediate chromosomal risk group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…CEBPA D-Mt was identified in the MPO-high group with high specificity, which was mutually exclusive with CBF-AML. Our previous analysis also indicated that CEBPA D-Mt was associated with high MPO-positivity in AML patients having normal karyotypes [14]. Therefore, the present study using a comprehensive analysis further confirmed the relationship between CEBPA D-Mt and MPO-positivity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CEBPA D-Mt was identified in the MPO-high group with high specificity, which was mutually exclusive with CBF-AML. Our previous analysis also indicated that CEBPA D-Mt was associated with high MPO-positivity in AML patients having normal karyotypes [14]. Therefore, the present study using a comprehensive analysis further confirmed the relationship between CEBPA D-Mt and MPO-positivity.…”
Section: Discussionsupporting
confidence: 85%
“…We previously revealed that the CEBPA double mutation (CEBPA D-Mt) was identified only among AML patients with a high percentage of MPO-positive blasts [14], and we also demonstrated that the MPO-positivity of AML blasts correlated with distinct DNA methylation profiling [15]. These findings suggest the presence of a specific relationship between MPO-positivity and gene mutations in AML.…”
Section: Introductionsupporting
confidence: 55%
“…Among the genes overexpressed in AML in the presented AML-array-based study, there were already-established AML markers, e.g., KIT , MYH11 , MN1 , MPO , SET and HOXA10 ( 44 , 47 , 48 ), genes associated with AML or potential biomarkers, such as STMN1 , CDK6 and ANGPT1 , or genes not yet discussed in the context of AML, such as RPLP0 or ENO1 , reported in neoplasms other than leukemia ( 49 , 50 ). As these genes often play fundamental roles in cell metabolism and function, their upregulation may be explained by the needs of the highly proliferating cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 However, the leukemia blasts of t(8;21) AML, which has a RUNX1-RNXT1 fusion protein, were shown to be strongly positive for MPO, 15,16 though RUNX1-RUNXT1 acts in a dominant-negative manner for RUNX1. 17 Similarly, the very strong association between high MPO positivity of blasts and the presence of CEBPA double mutation was demonstrated in AML patients, 18 despite the dominant-negative function of CEBPA double mutation for wild-type CEBPA. 19 The dominant-negative manner in RUNX1-RUNXT1 and CEBPA double mutation may not be involved in the regulation of MPO transcription in AML blasts.…”
Section: Introductionmentioning
confidence: 95%